2013
DOI: 10.1080/03630242.2013.831019
|View full text |Cite
|
Sign up to set email alerts
|

Information Needs, Seeking Behaviors, and Support Among Low-Income Expectant Women

Abstract: Previous studies have consistently found associations between low income and infant health outcomes. Moreover, although health information-seeking is a maternal behavior related to improved health outcomes, little is known about the health information-seeking behaviors and information needs of low-income pregnant women. The purpose of the current investigation was to examine the information needs, information-seeking behaviors, and perceived informational support of low-income pregnant women. Accordingly, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 43 publications
9
56
0
2
Order By: Relevance
“…Indeed, research in different contexts has proven personal preference toward social sources. For instance, Song, Cramer, McRoy, and May (2013) found that low-income pregnant women from Milwaukee (USA) cover their information needs through their families, while Huvila's (2013) research revealed that employees in a Nordic museum rely mainly on their colleagues. In addition, countless studies confirm that farmers use other members of their rural communities as information sources (see, for example, Agbongiarhuoyi et al, 2012;Nlerum, Albert, & Prince-Kaye, 2012).…”
Section: Information Seekingmentioning
confidence: 99%
“…Indeed, research in different contexts has proven personal preference toward social sources. For instance, Song, Cramer, McRoy, and May (2013) found that low-income pregnant women from Milwaukee (USA) cover their information needs through their families, while Huvila's (2013) research revealed that employees in a Nordic museum rely mainly on their colleagues. In addition, countless studies confirm that farmers use other members of their rural communities as information sources (see, for example, Agbongiarhuoyi et al, 2012;Nlerum, Albert, & Prince-Kaye, 2012).…”
Section: Information Seekingmentioning
confidence: 99%
“…In order to answer research questions 1 and 2 on the levels of information-need and information-seeking, a descriptive analysis was done. Table 2 above, presents the levels of information-need and informationseeking were categorized as high (35-50), moderate/average (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and Low (1-17). It was found out that majority of the pregnant women in the study area had moderate level of pregnancy information needs (58.3%) and information-seeking (52.2%).…”
Section: Resultsmentioning
confidence: 99%
“…It comprised of five sections: Section A -Demographic Data Inventory; Section B: Sources of Information on Antenatal Care -13 items; Section C: Information Seeking Needs -12 items; Section D: Perceived Problems Inhibiting Information Seeking Needs -10 items; Section E: Information Seeking Types -10 items. The levels of information-need and information-seeking were categorized as high (35-50), moderate/average (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and Low (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Maximum attainable score was 50.…”
Section: Instrument For Data Collectionmentioning
confidence: 99%
“…Topics included "Signs and symptoms of an abnormal pregnancy for my partner," "How to help my partner during childbirth," and "Jobs in my community." The list was adapted from a similar measure generated by Milwaukee Health Department nurses and used in previous work with low-income expectant women (Song et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Shieh, McDaniel, and Ke (2009) reported the top-five information needs of 84 low-income pregnant women to be early labor, danger signs, growth and development of baby, medications, and stress management. When choosing from a list of 22 pregnancy-related information topics, a sample of low-income expectant women selected (a) government/community resources and (b) jobs as the top two interest areas (Song, Cramer, McRoy, & May, 2013). Dervin, Harpring, and Foreman-Wernet (1999) reported the primary informational concerns of 10 pregnant, drug-addicted women to be the effects of drugs on the fetus, getting help, the behavior of others, and legal consequences.…”
Section: Information Needsmentioning
confidence: 99%